Penerapan Prinsip Utmost Good Faith Terhadap Sengketa Klaim Manfaat dalam Asuransi Jiwa (Studi Putusan Nomor 297/Pdt.G/2021/PN Jkt.Sel): Application of Utmost Good Faith Principle to Life Insurance’s Beneficial Claim Disputes (Study of Decision Number 297/Pdt.G/2021/PN Jkt.Sel) - Andini Savira Melati; N.G.N. Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2024)
Every activity carried out by humans always has risks, along with the development of technology and science, insurance has emerged which functions as a risk transfer. Insurance has terms and conditions that must be fulfilled, one of which is the principle of complete good faith which is an important aspect in administering insurance. This research to analyze the application of the principale utmost good faith in Decision Number 297/Pdt.G/2021/PNJkt.Sel and the resolution of insurance benefit claim disputes if the principle of utmost good faith not applied. The research was conducted using descriptive normative legal methods. Research results and discussion as well as conclusions Decision Number 297/Pdt.G/2021/PNJkt.Sel, the principle of utmost good faith has not been fully implemented by the insured or the insurer. The Insured doesn’t provide accurate information regarding his health condition and the Insurer doesn’t double check to ensure that the information written by the Insured is correct and accurate. Settlement of insurance benefit claim disputes if the principle of utmost good faith is not applied can be done through dispute resolution inside or outside court. In Decision Number 297/Pdt.G/2021/PNJkt.Sel, the insured chose to resolve the dispute by directly filing a lawsuit at the District Court.